COMPARISON OF EFFICACY OF TAMSULOSIN, ALFUZOSIN, AND SILODOSIN IN THE MANAGEMENT OF BENIGN PROSTATIC HYPERPLASIA - RETNAYYAN, APARNA; SREEDHARAN, SYAM; RETHINASWAMY, FREDRICK PAUL; NARAYAN NAMPOOTHIRI, HARISANKAR KARAKKAATTILLAM; MATHEW, BRIGHTY (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: This study was done to determine the efficacy of alpha-1 adrenoceptor blockers such as tamsulosin, alfuzosin, and silodosin in patients with the lower urinary tract symptoms (LUTS) due to benign prostatic hyperplasia (BPH) over 6 months by assessing change in international prostate symptom score (IPSS), quality of life scale for urinary symptoms (Bother score), and improvement in peak urine flow rate (Qmax) from baseline. We also tried to identify any adverse drug reactions (ADRs) caused by these drugs. Methods: A prospective observational study was conducted in 291 patients with LUTS secondary to BPH attending urology outpatient department of a tertiary care center for 1 year. Ninety-seven patients in each group received tamsulosin, alfuzosin, or silodosin once daily. IPSS, Qmax, and the quality of life scale for urinary symptoms by Bother score were assessed at 1st, 3rd, and 6th month of treatment period. ADR was noted and recorded in ADR reporting form. Results: IPSS, mean bother score, and mean Qmax showed significant improvement from the baseline in each follow-up visit at 1, 3, and 6 months for all the three groups, but maximum was for alfuzosin and was found to be statistically significant (p<0.001). Two patients developed adverse drug reaction during the study; asthenia in tamsulosin group and hypotension in Silodosin group. Conclusion: Patients on alfuzosin showed maximum improvement in the values of IPSS, Bother score, and Qmax in BPH patients as compared to tamsulosin and silodosin. Alfuzosin would be a better choice in the treatment of LUTS due to BPH.